Minimnya Penerapan Nilai-Nilai Pancasila Sebagai Sistem Filsafat Di Dalam Kehidupan Bermasyarakat (Studi Kasus Di Desa Pematang Sei Baru, Kecamatan Tanjung Balai, Kabupaten Asahan) - Sella Mita; Tiara Aulia Nurwana; Pani Andini; Elga Vasya Aura; Nurdin Nariga Sinulingga; Masrul Zuhri (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
this study aims to examine the low implementation of Pancasila values as a philosophical system within the community life of Pematang Sei Baru Village. Using a descriptive qualitative approach, observations, interviews, and documentation were conducted to obtain factual information regarding the community’s understanding of Pancasila values. Based on demographic data showing a total population of 4,494 people, with the majority working as fishermen, farm laborers, and students, the findings indicate that the internalization level of Pancasila values remains relatively low. Limited socialization, insufficient civic education, and the community’s focus on economic activities are identified as the main factors hindering the implementation of the values of divinity, humanity, unity, deliberation, and social justice. These results highlight the importance of developing more effective and sustainable strategies for Pancasila value education, particularly at the village level, to ensure its continued relevance as a philosophical system in national life.